Improved electrical transport in lightly Er-doped sol-gel spin-coating SnO2 thin films, processed by photolithography - Ravaro, Leandro Piaggi; Scalvi, Luis Vicente de Andrade [UNESP]; Boratto, Miguel Henrique [UNESP] (Springer, 2015)
Sol-gel spin-coating SnO2 thin films were deposited and processed through positive photolithography (liftoff), avoiding surface interaction with gaseous oxygen species and leading to samples with higher stability and data reproducibility, when submitted to electrical characterization. Processing includes: (1) a narrow conduction channel, (2) the assembly of electric contacts by ultrasound soldering, (3) deposition of an insulating layer, preventing the surface contact with atmospheric oxygen, which contributes for reliable measurements and the possibility of measuring SnO2 matrix properties without influence of adsorbed oxygen. Lightly Er-doped SnO2 sample (0.05 at.%), processed by this manner, has allowed the observation of a maximum about 50 K, in the temperature-dependent resistivity curve, which has not been found previously. This result is probably related to the combination of free electron concentration, which grows with temperature, and the grain boundary scattering, which decreases with temperature, and is the dominant mechanism for sol-gel SnO2. The processing also assures a remarkable reproducibility in the decay of photo-induced conductivity, yielding reliability to apply a modeling for the determination of important decay parameters, such as capture energy and grain boundary potential barrier.